Ethyl acetate extract of germinated brown rice attenuates hydrogen peroxide-induced oxidative stress in human SH-SY5Y neuroblastoma cells: role of anti-apoptotic, pro-survival and antioxidant genes - Azmi, Nur Hanisah; Ismail, Norsharina; Imam, Mustapha Umar; Ismail, Maznah (BioMed Central, 2013)
Background There are reports of improved metabolic outcomes due to consumption of germinated brown rice (GBR). Many of the functional effects of GBR can be linked to its high amounts of antioxidants. Interestingly, dietary components with high antioxidants have shown promise in the prevention of neurodegenerative diseases like Alzheimer’s disease (AD). This effect of dietary components is mostly based on their ability to prevent apoptosis, which is believed to link oxidative damage to pathological changes in AD. In view of the rich antioxidant content of GBR, we studied its potential to modulate processes leading up to AD.